Strategi Standarisasi dan Sertifikasi Produk Pangan Pada Pasar Rakyat Gianyar - Ida Ayu Made Dwi Susanti; Luh Putu Kirana Pratiwi; Ni Putu Sukanteri; Made Budiasa (Universitas Batangahari Jambi, 2023)
The agribusiness system consists of a production subsystem, a processing subsystem (upstream-downstream agro-industry), a marketing subsystem and supporting institutions. The revitalization of each agribusiness subsystem must continue to be improved due to the increasing consumer appetite for the agribusiness system (diversification), especially the subsystem of supporting institutions, namely the people's market. This can also occur due to changes in consumer behavior and perceptions of the people's market. This change is caused by the increasing development of technology and public communication in obtaining information. Especially, regarding the cleanliness and quality of food products. Through Interpretive Structural Modeling (ISM) analysis, a strategy for standardization and certification of food products was obtained at the Gianyar People's Market.Â